Research on digital library acceptance and continued use: review of theories/ Abd Latif Abdul Rahman and Adnan Jamaludin - Abdul Rahman, Abd Latif; Jamaludin, Adnan (Faculty of Information Management, Universiti Teknologi MARA, 2014)
The digital library is a new information system/technology that is beginning to be capitalized upon by libraries around the world to enhance information service provisions to their users. Although this information system/technology is still evolving, libraries have been offering this product for their clientele to use for some time. Since it is a new information system/technology with many implications for the organization, in this case specifically the library, the issue of its acceptance is of importance for its future development. This paper reviews some of the literature that is pertinent to research on the digital library acceptance and continued use research including the variable of intention to use of the digital library which also explains its continued use, and the significant variables interplay among these variables. Finally, the paper concludes all of previous studies have been inspired by the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and two adapted UTAUT models, namely Nationality Based Unified Theory of Acceptance and Use of Technology (NUTAUT), and the Service Oriented Unified Theory of Acceptance and Use of Technology (SOUTAUT). TAM and UTA UT are models that are generally used by researchers to measure acceptance and intention to use digital library systems.